2021
DOI: 10.1111/jipb.13051
|View full text |Cite|
|
Sign up to set email alerts
|

Plant plasma membrane‐resident receptors: Surveillance for infections and coordination for growth and development

Abstract: As sessile organisms, plants are exposed to pathogen invasions and environmental fluctuations. To overcome the challenges of their surroundings, plants acquire the potential to sense endogenous and exogenous cues, resulting in their adaptability. Hence, plants have evolved a large collection of plasma membrane-resident receptors, including RECEPTOR-LIKE KINASEs (RLKs) and RECEPTOR-LIKE PROTEINs (RLPs) to perceive those signals and regulate plant growth, development, and immunity. The ability of RLKs and RLPs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 254 publications
(625 reference statements)
0
35
0
Order By: Relevance
“…Plant PM-resident receptors recognize exogenous and endogenous signals, and then trigger proper responses to ensure a balanced modulation of development and stress adaptation [ 14 , 15 ]. Heterotrimeric G-proteins have crucial roles in regulating signaling pathways that are essential for growth and development [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant PM-resident receptors recognize exogenous and endogenous signals, and then trigger proper responses to ensure a balanced modulation of development and stress adaptation [ 14 , 15 ]. Heterotrimeric G-proteins have crucial roles in regulating signaling pathways that are essential for growth and development [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is conceivable that CERK1-4 generates a cell death signal in the apoplast, which could be sensed by a RLK or RLP-type receptor that interacts with the XLG2-AGB1-AGG1/AGG2 heterotrimeric G-protein complex. Many receptors characterized to date use BAK1 as a co-receptor and/or SOBIR1 as an adaptor kinase (Escocard de Azevedo Manhaes et al, 2021). Analysis of cerk1-4 double mutants with bak1 and sobir1 showed that the cerk1-4 signalling pathway does not rely on these two RLKs.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperimmunity phenotypes of the cerk1-4 mutant are associated with the extracellular part of the CERK1-4 protein (Petutschnig et al, 2014) and could potentially be perceived by a yet unknown RLK that signals through XLG2. Many of the RLKs and RLPs characterized to date use BAK1 as a co-receptor and/or SOBIR1 as an adaptor kinase (Escocard de Azevedo Manhaes et al, 2021). This encouraged us to test if the cerk1-4 cell death phenotype is dependent on BAK1 and SOBIR1.…”
Section: Cell Death Signalling In Cerk1-4 Is Not Mediated By Bak1 or Sobir1-containing Receptor Complexesmentioning
confidence: 99%
“…Receptors for cytokines are structurally diverse and mainly divided into five major superfamilies: type I (hematopoietin family) and type II (interferon family) cytokine receptors, tumor necrosis factor (TNF) family receptors, immunoglobulin superfamily receptors, receptor tyrosine kinases, and chemokine receptors (Wang et al 2009). In contrast, phytocytokines are usually perceived by cell surface-resident receptor-like kinases (RLKs), which contain an extracellular domain, a transmembrane region, and a cytoplasmic kinase domain resembling the animal receptor tyrosine kinases (Couto and Zipfel 2016;Escocard de Azevedo Manhaes et al 2021;Shiu and Bleecker 2001) (Table 1). Plant RLKs are classified into different subfamilies based on their extracellular domains.…”
Section: Phytocytokines Are Perceived By Cell Surface Receptorsmentioning
confidence: 99%